Loss of SNHG4 Attenuated Spinal Nerve Ligation-Triggered Neuropathic Pain through Sponging miR-423-5p - Xia Pan; Cheng Shen; Yayi Huang; Long Wang; Zhongyuan Xia (Hindawi Limited, 2020)
Neuropathic pain is an intractable comorbidity of spinal cord injury. Increasing noncoding RNAs have been implicated in neuropathic pain development. lncRNAs have been recognized as significant regulators of neuropathic pain. lncRNA Small Nucleolar RNA Host Gene 4 (SNHG4) is associated with several tumors. However, the molecular mechanisms of SNHG4 in neuropathic pain remain barely documented. Here, we evaluated the function of SNHG4 in spinal nerve ligation (SNL) rat models. We observed that SNHG4 was significantly upregulated in SNL rat. Knockdown of SNHG4 was able to attenuate neuropathic pain progression via regulating behaviors of neuropathic pain including mechanical and thermal hyperalgesia. Moreover, knockdown of SNHG4 could repress the neuroinflammation via inhibiting IL-6, IL-12, and TNF-α while inducing IL-10 levels. Additionally, miR-423-5p was predicted as the target of SNHG4 by employing bioinformatics analysis. miR-423-5p has been reported to exert significantly poorer in several diseases. However, the role of miR-423-5p in the development of neuropathic pain is needed to be clarified. Here, in our investigation, RIP assay confirmed the correlation between miR-423-5p and SNHG4. Meanwhile, we found that miR-423-5p was significantly decreased in SNL rat models. SNHG4 regulated miR-423-5p expression negatively. As exhibited, the loss of miR-423-5p contributed to neuropathic pain progression, which was rescued by the silence of SNHG4. Therefore, our study indicated SNHG4 as a novel therapeutic target for neuropathic pain via sponging miR-423-5p.